Economic Objections to the Policies of the Government of India in Supporting Cultural Motherhood - Anu Singh (Human Rights in the Global South (HRGS), 2023)
Women being equally valuable resources as labor, human capital, and entrepreneur, should be treated and given enough opportunities and free choices to improve the allocative efficiency of the economy. In these changing times, it is not enough to say no to choice—we must actively work toward defeating motherhood as an idea and practice. Per the data provided by the International Labour Organisation, female labor-force participation has gradually declined from 28.8% to 24% for females aged 15 and more. This paper highlights the economic consequences of gender-equality policies in India and the incapacity of the policymakers to analyze the consequences of such gender-insensitive policies. The author explains and discusses how society, especially the patriarchal family in India, is overutilizing a woman's motherhood, making women invest more than the optimal level of mothering on the one hand and making men perform less motherhood/parenthood than the socially efficient level. The researcher has collected primary and secondary data to analyze the government's leave policy. Upon interviewing more than 100 women and men directly or indirectly involved in childcare through WhatsApp and other calling mediums, author has analyzed that motherhood or mothering is heavily understood as the women's primary job rather than the equally shared and rarely efficiently distributed between the birth givers.